REFLECTIONS ON THE USE OF ARTIFICIAL INTELLIGENCE IN WORKS OF ART - I Made Marthana Yusa; Yu Yu; Tetiana Sovhyra (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: This paper aims to reflect on the use of Artificial Intelligence (AI) in works of art, examining its impact on the creative process, aesthetics, and audience reception, then provide a critical reflection on the use of AI in works of art, examining its potential benefits and drawbacks and exploring the ethical considerations involved. The paper examines the use of AI in works of art, with a focus on the methodologies and case studies that demonstrate the potential and challenges of this emerging field. Research methods: The paper presents case studies of notable artworks that utilize AI, discusses the potential benefits and drawbacks of AI in art, and explores the ethical considerations involved. Through a review of the literature and analysis of six case studies, we explore the aesthetic, technical, and social dimensions of AI-generated art, as well as the ethical and critical debates surrounding its production and reception. Findings: The paper concludes by emphasizing the importance of critical engagement and continued reflection on the use of AI in art. Our findings suggest that AI can offer new modes of creative expression and engagement, but also raise questions about the role of human agency and interpretation in the artistic process. Implications: AI-generated art offers new opportunities and challenges for artists, scholars, and audiences, and that future research should focus on developing ethical guidelines, exploring collaborative practices, and examining the social and political implications of AI-based art. Case studies of AI-generated art can help us understand the potentials and limitations of this field by providing specific examples of how AI is being used to create art, and how artists and audiences are engaging with these works. These studies can provide insights into the creative processes, technical challenges, and social implications of AI-generated art.